2013
DOI: 10.4236/jwarp.2013.510096
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality and Identification of Hydrogeochemical Processes within University of Lagos, Nigeria

Abstract: Water samples from twenty one boreholes were collected within University of Lagos and analyzed for physical properties, trace elements and cations using inductively coupled plasma optical emission spectrometry (ICP-OES). Physical analysis of the samples shows slight acidity and alkalinity with 78% of the samples exceeded recommended standards. They can be classified as fresh water based on TDS and EC. Chloride concentrations fall within water standards in most samples while Al, Na, Pb and Br exceeded recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
(16 reference statements)
2
5
0
Order By: Relevance
“…The concentration of nickel (Ni) in the water samples ranged from 0.01 to 0.07 mg/l. The values obtained are similar to those reported by Eni and Efiong (2011) and Odukoya et al (2013) in their respective works in parts of southern Nigeria. According to Pratt and Suarez (1990), Ni value of 0.20 mg/ l is the recommended maximum level.…”
Section: Resultssupporting
confidence: 81%
“…The concentration of nickel (Ni) in the water samples ranged from 0.01 to 0.07 mg/l. The values obtained are similar to those reported by Eni and Efiong (2011) and Odukoya et al (2013) in their respective works in parts of southern Nigeria. According to Pratt and Suarez (1990), Ni value of 0.20 mg/ l is the recommended maximum level.…”
Section: Resultssupporting
confidence: 81%
“…This suggests that the groundwater of some inland valleys may not be suitable for irrigation. This result is close to Odukoya et al (2013) results, who found that 33% of groundwater samples had MAR less than 50%. However, the result differs from those of Talabi et al (2014), who found that water samples were generally below the MAR value of 50%.…”
Section: Indexsupporting
confidence: 91%
“…The hydrogeochemical processes that are responsible for altering the chemical composition of groundwater vary with respect to space and time. Therefore, hydrogeochemical study is a vital tool for assessing its quality (Odukoya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%